The age of uncertainty : the U.S.-China-Japan triangle from Tiananmen (1989) to 9/11 (2001) - Vogel, Ezra F.; Yuan, Ming; Tanaka, Akihiko, 1954- (Harvard East Asian monographs., 2004)
A collaborative effort by scholars from the United States, China, and Japan, this volume focuses on how these three powers of the Asia-Pacific region adjusted their relations during 1989-2001 in the uncertain environment following Tiananmen and the end of the Cold War. The authors approach these questions from both a domestic and a foreign policy perspective. Three scholars describe the domestic context in each of the three countries. Each of the three bilateral relationships is examined by two scholars, one from each country involved.